Evaluation of the effect of different tangential methods on the performance of PID controller (PRESSURE) / Aina Saffiya Mohd Shahrom - Mohd Shahrom, Aina Saffiya (2023)
This study's objective was to evaluate the effects of various tangential techniques on the effectiveness of pressure controller’s open loop tuning. The process reactions curves obtained from the open loop tests were analysed and the resulting parameters for PID controller are determined based on three different tangential methods which are Tangent Method, Reformulated Tangent Method and Two-Point Method. In this experiment, the set point change test is performed to determine whether the process will become more or less stable by increasing the set point value by 10% of the process span. The Load Disturbance test came after, and this test involved changing a Manipulated Variable (MV). The disturbance will be crucial in deciding which approach has the fastest and most steady process. Changes in the setpoint variable (SV) also play an important role in determining the best approach, as changes in the setpoint variable and the load disturbance value are approximated. Based on settling time and IAE, the results section below shows the tangential method giving the fastest settling time and lowest IAE. In light of this, the tangential method provides greater process stability because the settling time is short, allowing the controller to quickly recover PV to SV after a disturbance, and the smaller IAE means less vibration.